ANALYSIS OF DETERMINANT OF BANK SYARIAH INDONESIA (BSI) MARKET SHARE BEFORE AND AFTER THE MERGER - Intan Naillul Farich (Airlangga International Journal of Islamic Economics and Finance, 2023)
Analysis Determinants Market Share of Indonesia Sharia Bank- Perspective Before and After Merger Bank Syariah Indonesia (BSI) is a bank formed by the government from the merging of BRI Syariah, BNI Syariah, and Bank Syariah Mandiri. This study will use structure conduct performance theory (SCP) to examince market share drivers in BSI before and after mergers. Market share is a metric for determining how profitable a firm is at a certain point in tim and in a ived region. ROA, NPF, BOPO, and FDR are some variables utilized to determine market share. Secondary data was employed in conjuction with quantitative approach approaches. The information used comes from the Financial Services Authority (OJK) and financial report of banks. Panel data regression applied to BSI before merger and multiple linear regression applied to BSI after merger were the models employed in this investigation. STATA 14 was used to do the experiment. The results of the regression data panels analysis revealed that the financial ratios utilized had a considerable impact on overall market share. As a result, our findings support the SCP theory that financial ratios used to gauge financial performance have an impact on market share. Following that, no significant effect on market share was found using estimates of the overall multiple linear regression variables ROA, NPF, BOPO, and FDR. The limited amount of time-series data used has an impact on insignificant outcomes. However, focusing just on each component reveals, dome promising potential in terms of BSI’s existence. As a result, the author came to the conclusion that the government’s merger is the best way to improve the performance of the Islamic finance business in Indonesia. Keywords: Structure- Conduct- Performance, Market Share, Merger